Dams and earthquake proceedings of a conference held at the Institution of Civil Engineers, London, on 1-2 October 1980. (Telford for the Institution, 1981)
Following on from the opening address by Marcus Fox, these papers are broken down into four sessions covering seismicity, materials behaviour when subjected to earthquake, structure behaviour when subjected to earthquake, and environment and risk including induced seismicity.
Keywords: Dams -- Earthquake effects -- Congresses.; elektronické knihy; electronic books